L’échec mondial de la lutte antidrogue : quelles leçonspour l’Afghanistan ? - Pierre-Arnaud Chouvy (EchoGéo)
Afghan opium production doubled between 2002 and 2008 in spite of a regime change in Kabul, the political support and military and economic aid of the international community, as well as counternarcotics measures. The history of international drugs in Asia is rich in counternarcotics failures, despite a few successes. Such past experiences are lessons to be learned for the Afghan authorities and the international community.